Effect of moisture conservation and nutrient management on rice production in rainfed lowland ecology of East and Southern Africa - SINGH, Y. P.; NHAMO, NHAMO; SINGH, R. K.; MURORI, R. (Journal of Soil and Water Conservation, 2022)
International Rice Research Institute, East and Southern Africa Regional Office, Tanzania conducted a baseline survey during 2008 to identify the causes of low productivity of rice in rainfed lowland ecology of east and southern African countries. The survey data revealed that poor moisture conservation and nutrient management practices are the major factors responsible for low productivity of rice in rainfed lowland ecosystem. To assess the effect of moisture conservation and nutrient management on productivity of rice under rainfed lowland ecosystem and to make a strategic moisture conservation and nutrient management plan to enhance rice productivity at Bagamayo-2, Bagamayo-3, Lupembe, Milema and Dakawa in different agro climatic regions of Tanzania during 2010. Moisture conservation through bunding increased water availability in upper soil layers at the time of critical dry spell. Substantial yield gains ranging from 0.34 t ha-1 to 0.93 t ha-1 were recorded following the use of improved technologies. The integration of moisture conservation and nutrient management technologies revealed that the average yield enhancement due to bunding only was 56.14% over no bunding. However, rice yield with good agricultural practices such as bunding + recommended dose of fertilizers ((N80:P2O540:K2O40) was 110.52%, 54.50%, 34.83% and 12.51% higher over no bunding and no nutrients (control), no bunding + 1 bag urea /acre 20 days after germination (Farmers practices), bunding+ no nutrient and no bunding + recommended dose of fertilizers. Relative yield gains decreased in the following order: bunding + recommended dose of fertilizers (110.5%)>no bunding + recommended dose of fertilizers (87.13%), bunding + no nutrient (56.14%), and no bunding + 1 bag (50kg) urea /acre 20 days after germination (Farmers practices). The gains obtained through combined effect of moisture conservation and nutrient management can be further enhanced through use of improved rice cultivars. It is concluded that moisture conservation through bunding enhanced 14.6 % grain yield over the farmer’s practices. Bunding + recommended dose of fertilizer gave 117% more income than the prevailing farmer’s practices. Therefore, it is recommended that bunding + recommended dose of fertilizers in two splits is advocated/encouraged/recommended for higher productivity of rice in rainfed lowland ecologies of east and southern African countries.